Pre-operative Serum CEA and CA19-9 Levels in Patients with Gastric Cancer: A Single-Center Experience - Atak, Ibrahim; Yegen, Serkan Fatih; Atak, Tuba; Guler, Alaattin; Polat, Lutfi; Samsa, Veysi (Eastern Journal of Medical Sciences, 2018)
Introduction: To evaluate the preoperative CEA and CA19-9 levels and their association with clinicopathologic features and mortality. Methods: This retrospective study was conducted on patients who underwent gastric surgery due to gastric adenocarcinoma from 2008 to 2015. Preoperative serum CEA and CA19-9 levels were compared according to the TNM classification and survival data were compared. Results: A total of 335 patients were included in the study with the mean age of 66.1±11.0 years. CEA and CA19-0 positivity were 29.1% and 28.1%, respectively. According to the CEA groups, T stages of the cases were statistically significant (p = 0.013). The rates of T stage 1 in group 1 (CEA positive) were significantly higher than the group 2 (CEA negative) (p=0.007). According to the CA19-9 positivity; rate of stage 2 was significantly higher in the group 1 (CA19-9 positive) (p=0.001); however, rates of stage 2 and 3 were significantly higher in the group 2 (CA19-9 negative) (p=0.004 and p=0.007, respectively). Mortality information could be accessed for 309 cases and 108 deaths (36%) were observed. The mean survival time was 45.21±2.42 months. No significant difference was observed between the groups (p>0.05). Conclusion: Patients with higher levels of CEA and CA19-9 seem to have higher grades of gastric cancer. However, CEA and CA19-9 level does not seem to be in association in our study population.